Generalized Fractional Order Complex Lorenz System-Based Dual Layer Security Enhancement Approach - K. Meera; N. Selvaganesan (IEEE Access, 2025)
The optimization of chaotic systems has gained significant importance to attain high complex attractors for cryptographic and communication applications. In this paper, the fractional order complex Lorenz system is considered and system parameters are optimized using sequential quadratic programming algorithm by considering a multi objective function. Since the higher value of the Lyapunov exponent and attractor geometry results in a system with strong chaotic characteristics, the reciprocal of the positive Lyapunov exponent and Kaplan-Yorke dimension is considered to generate a constrained weighted sum objective function. The highest Lyapunov exponent and fractal dimension obtained through optimization is 1.845 and 3.109 respectively. The optimized system is further used to generate hashed keys to encrypt and decrypt the rover imager data of the Chandrayaan-3 mission. A two layer enhanced security approach that combines cryptography and steganography is introduced, which includes 1) encryption of satellite image using advanced encryption standard algorithm with hashed key and 2) embedding the encrypted image using the least significant bit, discrete wavelet transform and spread spectrum based steganography to strengthen the security. Various performance metrics are evaluated and compared to analyze the performance of the proposed integrated algorithm. The state of the art of the proposed work is compared by considering standard images as the input. The proposed approach exhibits the highest key space, information entropy, MAE, MSE, PSNR, NPCR and UACI of $2^{700}$ , 7.9998, 100.314, 13827.4349, 6.7234, 99.776 and 39.061 respectively which are greater than the existing methods. Histogram analysis, correlation analysis and key space analysis are performed to ensure the efficiency of the enhanced security approach. In addition, IND-CPA and IND-CCA tests are performed which provide the adversary’s guessing accuracy of 48.4% and 48.7% respectively. This confirms the resistance of the proposed scheme against standard cryptanalytic attacks.